When Green Perspective Play a Role in Beauty Products through Online Shopping During Covid-19 Era - Salsabiila Thifaal Zayyaan; Ihsan Hadiansah; Karina Beiby Yulian (IDEAS: Journal of Management & Technology, 2023)
Indonesia has experienced a COVID-19 outbreak since the beginning of 2020. Covid-19 has had so many impacts, especially on consumer behavior. Therefore, the aim of this research focuses on the influence of green perspectives (environmental knowledge, peer influence, green packaging, green purchase behavior) to buy beauty products from environmentally friendly products in mediating on Green Purchase Intention through online shopping in this COVID-19 era. This study uses KMO to test validity in the pilot study and Smart-PLS to test the validity, reliability, and hypothesis of the variables in this study. To process the research, the researcher uses an internet questionnaire to collect all of the data surveys. There are 223 respondents, only 222 respondents who pass the screening question. Also, this study found that environmental knowledge, peer influence, and green packaging significantly influence green purchase intention. Also, environmental knowledge, peer influence, and green purchase intention significantly influence green purchase behavior. However, green packaging does not have a significant influence on green purchase behavior.